Bots para automatización de procesos de registro de damnificados por desastres naturales - Barrera Arotoma, Joel (2019)
This research aims to design a computer application with an integration of Bots technology, likewise, the integration of this technology is being designed, on the IBM Watson platform, to achieve the automation of the victims registration process by natural disasters in Peru. Currently, Bots technology in its Chatbot type is one of the most used, as it achieves several advantages, such as the reduction of time and costs, through the automation of organizational processes. Also, all these factors are considered for the development of the solution design. Therefore, the implementation of this technology in the creation of the prototype for the registration of victims of natural disasters will have the same qualities mentioned above, and will also support the massive task of obtaining information so that the respective authorities can provide support and timely attention to those affected by natural disasters. Therefore, the solution proposed in this research paper is considered of vital importance for the entire society, because it is very important to automate the registration of victims' incidents in the event of any event that may be arising. Likewise, the methodology that was used for the theoretical development of the research work, which has a quantitative approach, is also of the type applied under the quasi-experimental design. On the other hand, the use of the rapid application development methodology or RAD (rapid application development) is proposed for the solution of the mobile application with a bot integration, in its Chatbot type, this is an agile methodology in the process of Software development, likewise, the methodology allows the development of various prototypes in the shortest possible time, this is achieved through the use of different utilities of computer-assisted software or CASE (computer aided software engineering), consequently, the application computer science, generates great importance, because it allows to obtain data of the emergency in question in a fast and efficient way, with which the authorities can make more opportune decisions before these events.